Analisis Pemasaran Domba dari Tingkat Peternak Sampai Penjual Sate di Kabupaten Sleman - Suwarta, F.X. (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2009)
This aim of this research was to study marketing chain of sheeps from farmer, trader and satay seller and to study cost of marketing at each of instituted marketing and the revenue of farmer, trader and satay seller in Sleman regency, Yogyakarta. The research was conducted using a survey method. The respondents from sheep farmer, sheep trader and satay seller were 107, 37 and 64, respectively. Data were analyzed descriptively. The cost efficiency of marketing system was analyzed for marketing cost, margin, farmer’s share, market competition and profitability. The result showed that the most efficient of the distribution of the sheep marketing was from sheep, farmer, sheep trader and consumer. Margin analyzed showed that male sheep contributed larger margin than female sheep (19.78: 19.14%). The farmer share for sheep marketing revealed that female sheep contributed 80.85% while male sheep 80.21%. Coefficiency of market competition showed that sheep farmer had higher coefficiency competition than sheep trader both to female and male. Sheep farmer had higher net profit margin (NPM) level but had lower operating ratio level. Satay seller had lower NPM and higher operating ratio level. Key words : sheep, marketing, efficiency of marketing